Diabetic retinopathy among Omanis: Prevalence and clinical profile - Puspalata Agroiya; Abdul Hakeem Alrawahi; Fathimabeebi Pambinezhuth; Noor Bader Al Busaidi (Oman Journal of Ophthalmology, 2020)
PURPOSE: The aim of this study is to describe the prevalence, severity and clinical profile of diabetic retinopathy (DR) among Omani diabetic patients attending a tertiary care hospital. MATERIALS AND METHODS: This is a retrospective study involving the record review of diabetic patients attending the diabetes retina clinic of the National Diabetes and Endocrine Centre in the period between June 2015 and May 2016. Retinal evaluation of 442 native patients was conducted using direct ophthalmological examination and digital photography. DR was graded using the Early Treatment DR Study criteria. The statistical analysis was conducted using SPSS, version 20. RESULTS: The estimated total prevalence of DR was 31% (95% confidence interval: 26.6–35.3). Mild nonproliferative diabetic retinopathy (NPDR) constitutes 21.3%, while moderate-to-severe NPDR and proliferative diabetic retinopathy constitute 4.5% and 5.2%, respectively. The prevalence of vision-threatening diabetic retinopathy (VTDR) and diabetic maculopathy was 15.4% and 13.3%, respectively. Retinopathy was significantly associated with age, diabetes duration, Type 2 diabetes mellitus, coexisting comorbidities or complications, systolic blood pressure, glycated hemoglobin (HbA1c), fasting blood sugar, triglycerides, and albumin/creatinine ratio. In the regression analysis, age (P = 0.02), duration (P < 0.001), and HbA1c (P < 0.001) were independently associated with DR. CONCLUSIONS: The prevalence of DR and VTDR among Omani diabetics is high. Age, duration of diabetes, and HbA1c are the risk factors for the development of DR among Omanis. This emphasizes the importance of planning resources for different modalities of treatment of DR to face the future challenge.